Ion track etching in polyethylene-terephthalate studied by charge particle transmission technique. Issue 1 (1st February 2019) - Vacik, J.; Hnatowicz, V.; Havranek, V.; Fink, D.; Apel, P.; Horak, P.; Ceccio, G.; Cannavo, A.; Torrisi, A.
ABSTRACT: In the paper, thin films of polyethylene-terephthalate, pristine or irradiated with 170 MeV Xe + ions to the fluence of 10 5  cm −2, were etched in the mild 1 M NaOH medium at 60°C for different times. The main aspects of the etching process ( i.e. development of the pores, dependence of the foil thickness and transparency on the time of etching) were studied by the ion transmission technique (ion energy loss spectroscopy) that was previously introduced by the author's team. It has been shown that the transmission method makes it possible to closely monitor the development of the polymeric porosity and to determine the important parameters of the etching process ( e.g. etching rate along the latent tracks, bulk etching rate, radial etching rate, breakthrough, foil transparency). The measurement was carried out at the NPI Rez using the alpha particle microprobe on the Tandetron accelerator.